1989
DOI: 10.1136/jmg.26.12.781
|View full text |Cite
|
Sign up to set email alerts
|

Discordant, non-syndromic, congenital diaphragmatic defects in sibs.

Abstract: We report an Arab sibship of two brothers with non-syndromic, congenital diaphragmatic defects (CDD). The first had an extensive, left, Bochdalek-type hernia and the second hemidiaphragmatic agenesis; these were verified by surgical exploration and necropsy respectively. The parents are healthy second cousins. Other reported discordant cases of CDD are briefly reviewed. Con1genital diaphragmatic defects have been classified into (1) posterolateral (Bochdalek) hernia, (2) retrosternal (Morgagni) hernia, and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…[Butler and Claireaux, 1962; Welch and Cooke, 1962; Scott and Patterson, 1966; Passarge et al, 1968; ten Kate and Anders, 1970; Feingold, 1971; Harberg et al, 1976; Thomas et al, 1976; Crane, 1979; David et al, 1979; Pollack and Hall, 1979; Arad et al, 1980; Wolff, 1980; Gencik et al, 1982; Norio et al, 1984; Czeizel and Kovacs, 1985; Lipson and Williams, 1985; Toriello et al, 1985; Bocian et al, 1986; Toriello et al, 1986; Farag et al, 1989; Hitch et al, 1989; Carmi et al, 1990; Frey et al, 1991; Sripathi and Beasley, 1992; Narayan et al, 1993; Farag et al, 1994; Gibbs et al, 1997; Mitchell et al, 1997; Kufeji and Crabbe, 1999; Manouvrier‐Hanu et al, 2000]. As part of our own research over the last 5 years, we ascertained more than two dozen multiplex families in whom the diagnosis of a syndrome was not established.…”
Section: Evidence Of Genetic Contributions To Cdhmentioning
confidence: 99%
“…[Butler and Claireaux, 1962; Welch and Cooke, 1962; Scott and Patterson, 1966; Passarge et al, 1968; ten Kate and Anders, 1970; Feingold, 1971; Harberg et al, 1976; Thomas et al, 1976; Crane, 1979; David et al, 1979; Pollack and Hall, 1979; Arad et al, 1980; Wolff, 1980; Gencik et al, 1982; Norio et al, 1984; Czeizel and Kovacs, 1985; Lipson and Williams, 1985; Toriello et al, 1985; Bocian et al, 1986; Toriello et al, 1986; Farag et al, 1989; Hitch et al, 1989; Carmi et al, 1990; Frey et al, 1991; Sripathi and Beasley, 1992; Narayan et al, 1993; Farag et al, 1994; Gibbs et al, 1997; Mitchell et al, 1997; Kufeji and Crabbe, 1999; Manouvrier‐Hanu et al, 2000]. As part of our own research over the last 5 years, we ascertained more than two dozen multiplex families in whom the diagnosis of a syndrome was not established.…”
Section: Evidence Of Genetic Contributions To Cdhmentioning
confidence: 99%
“…Multiplex families with CDH-Numerous multiplex families with either isolated or complex CDH have been published [Butler and Claireaux, 1962;Welch and Cooke, 1962;Scott and Patterson, 1966;Passarge et al, 1968;ten Kate and Anders, 1970;Feingold, 1971;Harberg et al, 1976;Thomas et al, 1976;Crane, 1979;David et al, 1979;Pollack and Hall, 1979;Arad et al, 1980;Wolff, 1980;Gencik et al, 1982;Norio et al, 1984;Czeizel and Kovacs, 1985;Lipson and Williams, 1985;Toriello et al, 1985Toriello et al, , 1986Bocian et al, 1986;Farag et al, 1989;Hitch et al, 1989;Carmi et al, 1990;Frey et al, 1991;Sripathi and Beasley, 1992;Narayan et al, 1993;Farag et al, 1994;Gibbs et al, 1997;Mitchell et al, 1997;Kufeji and Crabbe, 1999;Manouvrier-Hanu et al, 2000]. Several of these families are consanguinous, making it likely that a single mutant gene is responsible for their disorder [Arad et al, 1980;Norio et al, 1984;Farag et al, 1989Farag et al, , 1994, though multifactorial inheritance cannot be ruled out as an explanation for familial clustering.…”
Section: Further Evidence That Cdh Has Genetic Determinantsmentioning
confidence: 99%
“…Several of these families are consanguinous, making it likely that a single mutant gene is responsible for their disorder [Arad et al, 1980;Norio et al, 1984;Farag et al, 1989Farag et al, , 1994, though multifactorial inheritance cannot be ruled out as an explanation for familial clustering. The discovery of mutations in the interferon regulatory factor 6 gene (IRF6) as the cause of lip pit or van der Woude syndrome could be a model for identifying multifactorial genetic changes contributing to CDH.…”
Section: Further Evidence That Cdh Has Genetic Determinantsmentioning
confidence: 99%
“…He reviewed the literature and found 4 other reports of families with 2 affected sibs born of normal parents and concluded that an autoso-ma1 recessive gene might be responsible, although no consanguinity could be documented for any family. As of 1992, there were at least 18 reports of familial agenesis of the diaphragm, some with a single other associated abnormality [Passarge et al, 1968;ten Kate and Anders, 1970;Feingold, 1971;Jensen and Altrogge, 1971;Daentl and Passarge, 1972;h a d et al, 1980;Wolff, 1980;Gencik et al, 1982;Bocian et al, 1983;Norio et al, 1984;Farag et al, 1989;Sripathi and Beasley, 19921. In 3 families, consanguinity was documented [ h a d et al, 1980;Norio et al, 1984;Farag et al, 19891 and remote consanguinity was suspected in another family [Daentl and Passarge, 19721.…”
mentioning
confidence: 99%